2016
DOI: 10.14814/phy2.13006
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of adipogenesis by neuropeptide Y during the later stages of chicken preadipocyte differentiation

Abstract: Neuropeptide Y (NPY) promotes adipogenesis in both birds and mammals, although mechanisms in avians remain unclear. The objective of this study was thus to evaluate effects of NPY on chick preadipocyte proliferation and differentiation. Preadipocytes were treated with 0, 1, 10, or 100 nmol/L NPY and gene expression and cellular proliferation were evaluated at 12, 24, and 48 h. At 12 h posttreatment, mRNA abundance of topoisomerase II alpha (TOP2A), and thioredoxin‐dependent peroxidase 2 was upregulated and NPY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…We also identified 145 DEMis and 660 DEMs between undifferentiated and differentiated preadipocytes. We found that top DEMs, such as FABP4 [40] and KLF5 [41] are involved in adipose tissue development of chicken. In the DEMis, gga-miR-128 [42] and gga-miR-223 [43] participate in regulating chicken preadipocytes differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…We also identified 145 DEMis and 660 DEMs between undifferentiated and differentiated preadipocytes. We found that top DEMs, such as FABP4 [40] and KLF5 [41] are involved in adipose tissue development of chicken. In the DEMis, gga-miR-128 [42] and gga-miR-223 [43] participate in regulating chicken preadipocytes differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The secretory peptide, Neuropeptide-Y (NPY), functions as an extracellular signal regulating adipogenesis by interacting with NPY receptors (Yang et al, 2008;Baker et al, 2009;Shipp et al, 2016). The expression of NPY promotes lipid deposition by promoting adipogenesis (Kuo et al, 2007;Baker et al, 2009;Zhang et al, 2015;Shipp et al, 2016) and inhibiting lipolysis (Valet et al, 1990;Park et al, 2014;Zhang et al, 2014;Liu et al, 2017). At the transcriptional level, NPY was the gene in turkey pmSCs most downregulated by cold stress during differentiation (Reed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…After the primary preadipocytes were obtained from the AF of chickens (2–4 weeks old; Institute of Animal Science, CAAS) according to a previously reported protocol [ 17 ], cells were cultured in DMEM/F12 containing 10% FBS. At 100% confluence, cells in three replicate wells of six-well culture dishes were treated with either 0 or 30 ng/mL testosterone.…”
Section: Methodsmentioning
confidence: 99%